Tinjauan Yuridis Terhadap Tindak Pidana Pencemaran Nama Baik Terhadap Partai Aceh (Analisis Kasus Putusan Nomor : 184/PID/2017/PT,BNA - yowana atika wana (Jurnal Hukum Lex Generalis, 2025)
Defamation is an act that is prohibited by law because it can harm a person's good name and honor as regulated in Article 27 paragraph 3 and 45 paragraph 3 of Law of the Republic of Indonesia number 11 of 2008 concerning electronic transaction information. It is also found in Article 310 paragraphs 1 and 2 of the Criminal Code, Also contained in Article 310 paragraphs 1 and 2 of the Criminal Code, the aim of this research is to examine and understand the application of defamation law to Acehnese as well as the judge's considerations in imposing criminal sanctions on perpetrators of defamation. This type of research uses normative juridical using qualitative methods. From the results of this research, firstly, posts or images of writing were found that were intentionally caused by annoyance and hurt feelings, secondly, in the judge's consideration in making a decision based on the facts revealed.